Pengaruh pemberian isocaloric fructose restriction dan kapsul daun kelor (Moringa oleifera) terhadap nilai antropometri pada kelompok obesitas usia 19-50 tahun - Hanifah Mardhotillah; Diana Nur Afifah; Adriyan Pramono (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The incidence of obesity has increased due to changes in lifestyle and eating patterns. Excessive consumption of fructose is a major contributor to obesity. Portion control can be used as a short-term strategy for weight loss. Limiting fructose consumption and using natural ingredients such as moringa leaves can be used in weight management in obese sufferes.Objectives: to determine the effect of administering isocaloric fructose restriction and moringa oleifera leaf capsules on antropometric values in the obese group.Methods: Single randomized controlled trial with pre-post test. The research conducted in Kuningan, West Java in August-October 2023 involving 24 subject with obesity. Subjects were divided into 2 groups, namely control (n=12) which was given isocaloric fructose restriction 1800 kcal and treatment group (n=12) given isocaloric fructose restriction 1800 kcal and Moringa oleifera capsule 2400mg/day for 9 days. Anthropometric measurements in the form of body weight, height and abdominal circumference were taken twice. Data analysis used Dependent t test at 95% CI.Results: There was a decrease in body weight and BMI before and after the intervention. The decrease in body weight and BMI was more significant in the treatment group (p<0,05).Conclusion: There is an effect of giving isocaloric fructose restriction and moringa leaf capsules on body weight and BMI.KeywordsObesity, Fructose, Moringa oleifera